Dynamics of currents and biological scattering layers around Senghor Seamount, a shallow seamount inside a tropical Northeast Atlantic eddy corridor. (May 2021) - Mohn, Christian; White, Martin; Denda, Anneke; Erofeeva, Svetlana; Springer, Barbara; Turnewitsch, Robert; Christiansen, Bernd
Abstract: Biophysical interactions of the mesopelagic fauna and hydrodynamic features were investigated at a shallow, tall seamount in the tropical Northeast Atlantic based on data from three inter-disciplinary surveys collected between 2009 and 2015. Senghor Seamount is located close to the equator in a unique but underexplored oceanographic setting, where classical seamount effects are expected to be small. Shipboard Acoustic Doppler Current Profiler (ADCP) and remote sensing data revealed flow phenomena strongly varying over different temporal and spatial scales. The quasi-steady, longer period flow at the seamount was largely unchanged by flow-topography interaction with the exception of a persistent and recurring shadow zone of weaker currents downstream of the summit. Senghor Seamount is exposed to energetic mesoscale eddy activity in surrounding waters with potentially large physical and biological implications. At higher frequencies, tidal currents interacting with the seamount generated large-amplitude internal waves propagating horizontally and vertically away from the summit. Analysis of acoustic backscatter data and micronekton biomass displayed prominent near-surface night time and deep (>400 m) day time scattering layers associated with the diurnal vertical migration of the mesopelagic fauna. An intense and previously unreported aggregation of acoustic scatterers was detected in the depth range 150–300 m inside a radius of 3 km along the upper slopes of the seamount summit. ADCP measurements over a full semi-diurnal tidal cycle suggest that biophysical interactions were present in near-seafloor waters around the upper seamount as evidenced by plankton distributions that were modified by topographic blocking during descent and aggregation in waters characterised by internal waves and enhanced tidally-driven energy dissipation. Highlights: Energetic internal waves and eddy-driven far field flow dominated seamount currents. Planktonic and micronektonic acoustic scatterers were aggregated in three characteristic depth layers. Persistent aggregation was recorded at intermediate depths along the upper seamount slopes. Micronekton distribution was influenced by topographic blockage during descent and response to internal tides.